2015
DOI: 10.18553/jmcp.2015.21.12.1149
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Model to Identify Individuals Likely to Have Undiagnosed Chronic Obstructive Pulmonary Disease Using an Administrative Claims Database

Abstract: This claims-based predictive model provides an acceptable level of accuracy in identifying patients likely to have undiagnosed COPD in a large national health plan. Identification of patients with undiagnosed COPD may enable timely management and lead to improved health outcomes and reduced COPD-related health care expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Some studies have developed predictive models to identify patients with undiagnosed COPD using administrative claims. 12 , 13 A COPD-predictive model described by Mapel et al 12 had a PPV of 23% and NPV of 95.4%, while a model developed by Moretz et al 13 had a PPV of 73% and NPV of 66%. The current model had a PPV of 48.1%, between values reported by Mapel et al and Moretz et al, suggesting that approximately one in two patients identified will have a severe COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have developed predictive models to identify patients with undiagnosed COPD using administrative claims. 12 , 13 A COPD-predictive model described by Mapel et al 12 had a PPV of 23% and NPV of 95.4%, while a model developed by Moretz et al 13 had a PPV of 73% and NPV of 66%. The current model had a PPV of 48.1%, between values reported by Mapel et al and Moretz et al, suggesting that approximately one in two patients identified will have a severe COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Predictive models to identify individuals likely to have COPD have been developed previously. 12 , 13 Similarly, observational and retrospective claim-based studies have attempted to identify factors associated with a risk of future exacerbations. These studies suggest that patients with a history of one or more exacerbations leading to hospitalizations have a high risk of future exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…A predictive model was developed by Moretz et al using Humana’s administrative claims database for identifying patients likely to have undiagnosed COPD 10. This claims database includes members enrolled in commercial or Medicare Advantage plans with prescription drug benefit (MAPD) plans.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal breathing sounds (such as crackles, rhonchus, and wheezing sounds) are usually considered as indicator symptoms in chronic respiratory diseases [ 1 ], such as chronic obstructive pulmonary disease (COPD), chronic bronchitis, and bronchial asthma, etc. For these diseases, unnecessary secretions (such as sputum) would be produced in the respiratory tract and then cause chronic inflammation leading to airway obstruction.…”
Section: Introductionmentioning
confidence: 99%